2017
DOI: 10.1016/j.it.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Bioengineering: Gut in a Dish

Abstract: Studying the interactions between commensal microbes and host intestinal tissue networks is challenging due to the complexity and inaccessibility of the system. A recent study reports a novel organ culture system that will enhance our ability to dissect these interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The authors were able to maintain both aerobic and anaerobic bacterial growth for the duration of the study (24 h) and identified immune and nonimmune transcriptional and functional responses to bacterial stimulation; thus, proteomics characterization of the system could be readily applied. While in its present form, this system has not yet been developed for human organs; advances in humanized mouse models may permit its application in human cell/tissues responses …”
Section: Model Systems To Study Bacteria Host–bacteria Interactions A...mentioning
confidence: 99%
“…The authors were able to maintain both aerobic and anaerobic bacterial growth for the duration of the study (24 h) and identified immune and nonimmune transcriptional and functional responses to bacterial stimulation; thus, proteomics characterization of the system could be readily applied. While in its present form, this system has not yet been developed for human organs; advances in humanized mouse models may permit its application in human cell/tissues responses …”
Section: Model Systems To Study Bacteria Host–bacteria Interactions A...mentioning
confidence: 99%